Peningkatan Pengetahuan tentang Diet Hipertensi melalui Pendidikan Kesehatan Model BASNEF - Lia Eryani; Rahmawati Ramli; Rizqy Iftitah Alam; Andi Yuliana (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
BASNEF model health education is an independent nursing action to help clients both individuals, groups, and the most comprehensive community used to investigate and encourage new behavior in the community. This study aims to determine the effect of BASNEF model health education on knowledge about hypertension diet in the elderly at Bangkala Antang health center 2023. This study used a preexperiment design with a Pretest-Postest Control-Group Design. And divided into two groups, namely the experimental group and the control group. The sample in this study used puposive sampling with a total sample of 36 people. The results showed that there was a significant effect of BASNEF model health education on knowledge about hypertension diet in the elderly at Bangkala Antang health center p value (p=0.000).The conclusion of this study is that there is an effect of health education using the BASNEF model on knowledge of hypertension diet in the elderly at Bangkala Antang health center, this model is very suitable to be applied by Bangkala Antang health workers in order to increase knowledge related to hypertension diet in the elderly who suffer from hypertension.